The Impact of Employee Performance Appraisal Systems on Healthcare Service Quality: A Literature Review - Ni Wayan Sri Artati; Lalu Sulaiman; Sastrawan Sastrawan (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
This study aimed to evaluate the impact of employee performance appraisal systems on healthcare service quality in hospitals. A systematic literature review was conducted by analyzing 12 peer-reviewed articles published between 2020 and 2025, selected from prominent academic databases such as PubMed, Scopus, and ScienceDirect. These articles were reviewed based on their relevance to the relationship between performance appraisals and healthcare quality. The review identified that well-structured performance appraisal systems significantly contribute to enhancing employee motivation, which directly influences the overall quality of healthcare services. Transparent, objective, and fair appraisal systems, when implemented effectively, help align employee goals with organizational objectives, leading to better patient care. However, the study also highlighted several challenges, including bureaucratic barriers, a lack of evaluator training, and cultural misalignment, which hinder the successful implementation of these systems in hospitals. Additionally, the review found that performance appraisals, when conducted periodically with constructive feedback, encourage continuous professional development and improve service delivery. The study concluded that for a performance appraisal system to be truly effective, it must be ongoing, incorporate clear communication, and be adaptable to the hospital’s organizational culture. Future research should focus on longitudinal studies to assess the long-term effects of performance appraisals on healthcare quality. Furthermore, combining qualitative and quantitative methods may provide a deeper understanding of the complex interactions between performance appraisals and employee performance in healthcare settings.